Pharmaceutical Pricing Policy in Greece: Toward a Different Path - Souliotis, Kyriakos; Papageorgiou, Manto; Politi, Anastasia; Athanasiadis, Athanasios (Frontiers in Public Health, 2016)
Background: Affordable, accessible and innovation-promoting pharmaceutical care is essential to the operation of a sustainable health system. External reference pricing (ERP), a common pharmaceutical policy in Europe, suffers today from indigenous weaknesses that may cause market distortions and barriers to care, burdening mostly the weak economies, and hence, raising ethical and political worrying. Objectives and Methods: A non-randomized experiment was conducted, in order to examine the influence of flexible and adaptable to health systems’ affordability ERP structures. Outcomes were assessed by measuring deviations from Greek prices’ level ex ante, as well as effects on pharmaceutical markets affiliated to the European ERP system. Results and Conclusions: Pharmaceutical pricing models that fit prices to income and affordability are better in all aspects, as they produce fairer results, while resulting in low external costs for the European ERP network as a whole. Small sets of reference countries are preferred to large baskets, as they produce similar results, while presenting better qualities by increasing the flexibility of the reimbursement system and the transparency of the market.